THE MUSEUM IN MOTIONOR AN ANALYSIS OF GUZAL BEGIM’S POEM “THERE IS A SEA MUSEUM INSIDE ME” (International journal of artificial intelligence, 2026)
This article is devoted to the creative work of Go‘zal Begim, one of the distinguished representatives of contemporary Uzbek poetry. The study analyzes the poet’s poetic thinking and the nature of the literary text in their organic interrelation. The semantic and poetic essence of the poem is interpreted in harmony with the author’s personality, inner psychological state, and aesthetic worldview.The article deliberately moves away from rigid and formulaic analytical methods characteristic of traditional literary criticism and instead employs modern, complex, and interdisciplinary methodological approaches to the interpretation of poetic texts. In particular, the semantic layers, symbolic system, as well as the psychological and aesthetic components of the poetic text are revealed through an integrative mode of analysis.Rather than reiterating fixed hypotheses and one-sided interpretations previously applied to the poet’s works, the author conceptualizes poetry as a dynamic, multifaceted aesthetic phenomenon capable of exerting a simultaneous impact on the reader’s cognition and emotional experience. The study substantiates the evolving nature of the poetic text and its capacity to generate new meanings across different periods and within diverse readerly consciousnesses.Thus, the article is aimed at examining Go‘zal Begim’s oeuvre from the perspective of contemporary literary studies and is significant for its application of innovative scholarly concepts to the analysis of poetic thinking and aesthetic perception.